The Africa Growth and Opportunity Act and its Rules of Origin : Generosity Undermined? - Subramanian, Arvind; Mattoo, Aaditya; Roy, Devesh (Washington, D.C. : International Monetary Fund, 2002)
This paper describes the United States recently enacted Africa Growth and Opportunity Act (AGOA) and assesses its quantitative impact on African exports. The AGOA expands the scope of preferential access of Africa's exports to the United States in key areas such as clothing. However, its medium term benefits estimated at about USD 100-USD 140 million, an 8 11 percent addition to current non-oil exports would have been nearly five times greater (USD 540 million) if no restrictive conditions had been imposed on the terms of market access. The most important of these conditions are the rules of origin with which African exporters of clothing must comply to benefit from duty-free access.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet